Bearing capacity of shallow foundations: a focus on the depth factors in combination with the respective N-factors - Pantelidis, Lysandros (My University, 2024)
The ongoing refnement of bearing capacity equations remains pivotal in soil mechanics and foundation engineering, refecting its critical role in ensuring design efcacy and construction safety. This study conducts a thorough evaluation of classical bearing capacity methods—Terzaghi, Meyerhof, Vesic, and Hansen—and methods included in various design standards, such as EN1997:2004, prEN1997:2023, GEO, AASHTO, FHWA, and API. It explores the performance and applicability of these approaches, identifying areas for potential improvement. In response to identifed challenges, the paper proposes the integration of a unifed depth factor. This new factor is designed to be applicable across all N-terms, providing a more versatile and accurate tool for bearing capacity predictions. Unlike the original depth factors unique to each method, which may not fully address complex soil and footing conditions, the unifed depth factor is developed to enhance prediction accuracy for a wide range of conditions, including both fexible and rigid footings under varying fow rules (ψ=0 and ψ=φ). This depth factor corrects for modeling errors, emphasizing the importance of pairing the correct set of N-factors with their corresponding depth factor. By ofering a singular depth factor that aligns with the outcomes of fnite element analysis, this paper not only simplifes the computational process but also enhances the accuracy of bearing capacity predictions across a diverse range of soil conditions and footing types. The comparative analysis, based on fnite element analysis, validates the proposed method’s efectiveness, showcasing its potential to signifcantly refne foundation design practices by comparing it with both traditional and newly developed depth factors.
Keywords: Bearing capacity; Strip footings; Non-associated fow rule; Associated fow rule; Unifed depth factor; Rigid and fexible footings